Authoritarian Parenting dalam Film Drama Keluarga Indonesia - Intan Anggraeny; Monika Pretty Aprilia (MUKASI: Jurnal Ilmu Komunikasi, 2022)
This study aims to determine the frequency of authoritarian parenting in family drama films and to find out how the film frames the parenting style, especially authoritarian parenting in each scene so that the messages contained can be easily understood by the audience. This research was researched with descriptive quantitative content analysis method. This study also uses four indicators of authoritarian parenting from Robinson, Roper, Mandleco, & Hart, 1995, which include indicators of punishment, release, direction and discipline. The samples in this study are scenes taken from films that aired in 2019 – 2021, namely, NKCTHI, Imperfect, Geez & Ann, Dignitate and Maripossa, with a total of 36 scenes. Calculation of the reliability test on the measuring instrument using two coders, with a sample of 23 scenes. The coding results show that the coding sheet is reliable with the results, in Maripossa film of 0.75 (75%), Imperfect film of 1.0 (100%) and NKCTHI film of 0.8 (80%). The results of the study stated that the indicator that has the highest calculation is the direction indicator with 50%, then 30.4% discipline, 17% vent, and 2.6% punishment. This research can represent social problems related to the harmonious relationship between parents and children, with appropriate framing and emotional play in each scene that makes the message conveyed well through film media.